2015
DOI: 10.1111/jgs.13626
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Consumption and Risk of Frailty in Older Adults: A Prospective Cohort Study

Abstract: 19Background/Objectives. A high quality diet is associated with lower risk of frailty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 38 publications
0
55
0
3
Order By: Relevance
“…Several publications have revealed that healthy diets are associated with better quality of life [13, 15, 16]. For instance, studies have shown that individuals with a higher score for adherence to a Mediterranean-style diet [17, 18] and higher consumption of low-fat milk and yogurt [19] have lower odds of developing frailty, while a variety and quality of diets in older people [20] is increased by factors, such as social resources, money and help from friends and neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have revealed that healthy diets are associated with better quality of life [13, 15, 16]. For instance, studies have shown that individuals with a higher score for adherence to a Mediterranean-style diet [17, 18] and higher consumption of low-fat milk and yogurt [19] have lower odds of developing frailty, while a variety and quality of diets in older people [20] is increased by factors, such as social resources, money and help from friends and neighbors.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant relationship between the consumption of fruit and vegetables and the existence of anemia and serum folate levels (p>0.05). Milk and milk products, which are important sources for vitamin A, folic acid, vitamin B 12 , riboflavin, and vitamin B 6 , play a role in red blood cell formation 31 . In a study carried out in Spain on individuals aged 80 and over, it was determined that the daily consumption of milk, yoghurt, and cheese were 1.4 portions, 1.2 portions, and 0.6 portions respectively 32 .…”
Section: Resultsmentioning
confidence: 99%
“…During follow-up, 95 individuals died and 115 were lost, so information was obtained for only 2,404 persons in 2012. The socio-demographic, lifestyle and clinical characteristics at baseline were similar in those who provided updated information on frailty at 2012 and those who did not (13). …”
Section: Methodsmentioning
confidence: 99%